2019
DOI: 10.1038/s41598-019-49274-y
|View full text |Cite
|
Sign up to set email alerts
|

The association of gut microbiota characteristics in Malawian infants with growth and inflammation

Abstract: We tested the hypotheses that a more mature or diverse gut microbiota will be positively associated with infant growth and inversely associated with inflammation. We characterized gut microbiota from the stool samples of Malawian infants at 6 mo (n = 527), 12 mo (n = 632) and 18 mo (n = 629) of age. Microbiota diversity and maturity measurements were based on Shannon diversity index and microbiota for age Z-score (MAZ), respectively. Growth was calculated as change in Z-scores for weight-for-age (WAZ), length-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(49 citation statements)
references
References 46 publications
4
45
0
Order By: Relevance
“…The prevalence of bifidobacteria is much higher in lower-income regions of the Southern Hemisphere compared with high-income countries of the Northern Hemisphere ( 21–23 ). In our study population, bifidobacteria comprise the largest proportion of microbes in the first year of life ( 40 ) and are associated with infant growth ( 41 ). Both 2′FL and LNnT have been shown to enhance the growth of beneficial bifidobacteria ( 32 , 42 , 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of bifidobacteria is much higher in lower-income regions of the Southern Hemisphere compared with high-income countries of the Northern Hemisphere ( 21–23 ). In our study population, bifidobacteria comprise the largest proportion of microbes in the first year of life ( 40 ) and are associated with infant growth ( 41 ). Both 2′FL and LNnT have been shown to enhance the growth of beneficial bifidobacteria ( 32 , 42 , 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies in undernourished infants and their microbiota have found lower microbial diversity with stunting (71), underweight and wasting (57), or severe acute malnutrition (30). Other studies have found no differences in diversity in mice which received microbiota from either severely stunted or nonstunted infants after 30 days postcolonization (72), or in Malawian infant weight-for-age Z-scores (WAZ) between 12 and 18 months of age (73). A potential explanation for our results is our small sample size, or some unmeasured environmental factor(s) may have influenced the association between WLZ and the gut microbiota in this cross-sectional analysis.…”
Section: Discussionmentioning
confidence: 99%
“…All stool sample collection and sequencing occurred prior to the current data analysis. Sample collection and sequencing was performed as previously described 61 . Briefly, infant stool samples were collected at 6 months, 12 months, and 18 months of age.…”
Section: Methodsmentioning
confidence: 99%
“…In the two control groups, women received iron and folic acid (IFA) during pregnancy only or multiple micronutrients (MMN) during pregnancy and the first six months postpartum, but their infants did not receive any supplement. The effects of the intervention on infant growth 20 , characteristics of the child’s gut microbiome 59 , and maternal breast milk composition 60 have been published previously, as well as analyses that relate aspects of gut microbiome composition to infant growth and inflammation 61 , morbidity 62 , and environmental factors 63 . This analysis examines whether variability in infant gut microbiota composition, such as the ratios of taxa described above, may contribute to variability in response to the intervention.…”
Section: Introductionmentioning
confidence: 99%